kehidupan sosial ekonomi pekerja perempuan pengolah pala - Rizki Andika; Mahmuddin Mahmuddin (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2017)
ABSTRACT  This thesis aims to determine the socio-economic conditions of women worker of nutmeg in the village of Hilir Tapaktuan subdistrict, south aceh and the factors causing the women to work in processing nutmeg in downstream village tapaktuan district south aceh. This research uses James S Coleman’s rational choice theory as a fundamental feature of society. This research is descriptive research, using qualitative approach. Data obtained through in-depth interviews with information who meet the criteria of research subjects, and relevan in providing information needed in this study. The women who work in this nutmeg processing industry are majority of the local people. They work every day starting from 08.00 am until finished the worker are based on economic factors to meet their family needs and limited employment factors also require that they can not choose other jobs in the downstream village of Tapaktuan south aceh. The monthly income of nutmeg workers of processing industry is Rp. 750.000. Women of nutmeg workers are required to be able to share their time, between their home work and their job and usually before they got to work they have tod do their basic duties as housewives such as preparing breakfast for their family and also preparing their husband and children needs.Keywords: Social Life, Economics And Female Workers